Effect of neurodynamic mobilization techniques in patients with diabetic neuropathy - Ahmed Magdy Alshimy; Saied Mohamed Ibrahim; Lamis Ahmed Osama; Hosam Magdy Metwally (Termedia Publishing House, 2023)
Purpose Neurodynamic mobilization is a set of passive or active movements aimed at restoring the neural system's ability to bear the normal compressive, friction, and tensile stresses encountered in daily life. This study aimed to investigate the effect of neurodynamic mobilization on sensory and motor nerve conduction studies, pain, and functional activity in patients with type 2 diabetic neuropathy (DN). Methods A total of 42 patients were randomly assigned to the neurodynamic mobilization group (NMG) or selected therapy program group (STPG). Electrophysiological measurements for median sensory and tibial motor nerve conduction velocity, and functional activity were conducted using the Katz Index of Independence, while pain was evaluated using the visual analogue scale. Results Improvement was noted in the post-treatment median sensory ( p = 0.002) and tibial motor ( p < 0.001) nerve conduction velocity, functional activity ( p < 0.001), and pain ( p < 0.001), and a statistically significant difference was demonstrated for the NMG, but not for the STPG. Conclusions Neurodynamic mobilization improved the sensory and motor nerve conduction velocity, functional activity, and pain in patients with type 2 DN.